Legal Review of Marriages based on Religious Beliefs Not Recognized by The State in Indonesia - Happy Sturaya Quratuainniza; Dwi Aryanti Ramadhani (Jurnal Daulat Hukum, 2025)
This study examines the implementation of marriage recognition for followers of indigenous religions, including those formally recognised by the State and those not recognised, and the legal consequences in certain situations. In Indonesia, interfaith marriages are often considered valid under their respective traditions and beliefs. Still, they are not officially recognised by the State, as Marriage Law Number 1 of 1974 recognised only six religions. This difference has led to various legal issues, including uncertainty about the couple’s marital status and their children, loss of inheritance rights, and obstacles to using public facilities and administrative processes. This study employs a normative legal approach, with a specific focus on the Constitutional Court’s decisions. The results of marriages show that legal recognition of marriages between members of indigenous religions remains limited and does not guarantee legal equality. According to the analysis, amending the Marriage Law and Population Administration Law to promote greater inclusivity regarding customary belief systems is a viable solution. The novelty of this research lies in the conflict between Article 2 paragraph (1) of the Marriage Law and Constitutional Court Decision Number: 146/PUU-XXII/2024, which states that believers are entitled to administrative recognition if their teachings and worship practices are deemed similar or closest to one of the religions recognised by the State. Thus, legal equality cannot be achieved through court decisions in a civil law system.